Comparative analysis of altered weather parameters on Phoma leaf blight (Phoma sojicola) of soybean (Glycine max) - SUBAYA MANZOOR; F A BHAT; Z A BABA; T A WANI; SUMILA GUL; HUMIRA GULZAR (The Indian Journal of Agricultural Sciences, 2022)
Development of a plant disease like Phoma blight (Phoma sojicola) of soybean ]Glycine max (L.) Merr.] in time and space is a variable, largely depending on environmental factors like temperature, precipitation and humidity. Considering importance of this disease, understanding its dynamics via mathematical and statistical models will help in disease forecasting and prevention of yield losses. To serve this objective, present study on epidemiology of Phoma leaf blight of soybean was carried out under natural epiphytotic conditions on 2 soybean cultivars (Shalimar soybean 1 and Kashmir local) at research farm of Sher-e-Kashmir University of Agricultural Sciences and Technology of Jammu, Jammu and Kashmir during rainy (kharif) season 2019 and 2020. Weather factors significantly influenced disease development irrespective of crop cultivar as revealed by correlation matrix between weekly disease score and weather of preceding one and preceding three weeks. Disease intensity was found positively correlated with RH and rains while as the correlation with temperature was negative. It followed similar trend with all the three sets of weather parameter as weather of preceding one week and that of 3rd and preceding three weeks have contributed to the extent of 57, 50 and 51%, respectively. The study further reveals that optimum temperature for all the events of pathogenesis besides inoculum dispersal in this case lies below 25oC while as the optimum relative humidity must be above 90% and this all is made possible when it rains at least once a week in the summer.